Hypolimnetic oxygenation 5. Copper, zinc, iron, and manganese declines in Camanche Reservoir downstream of an abandoned mine. (9th June 2022) - Horne, Alex J.; Jung, Rodney
Abstract: Horne, AJ, Jung R. 2022. Hypolimnetic oxygenation 5. Copper, zinc, iron, and manganese declines in Camanche Reservoir downstream of an abandoned mine. Lake Reserve. Manage. 38:139–149. An abandoned mine upstream of Camanche Reservoir in California had increased sediment copper (Cu) and zinc (Zn) concentrations by 10-fold. Regulators and environmentalists claimed that a hypolimnetic oxygenation system (HOS) on the reservoir bed would stir sediments and increase metal toxicity in the hypolimnetic water supplied to steelhead and Chinook salmon in the Mokelumne River and its large fish hatchery. On the contrary, after HOS, small decreases in the concentrations of Zn and Cu and large decreases in iron (Fe) and manganese (Mn) occurred. Before HOS, ΣCu concentrations were relatively low (mean deep, 3.3 µg/L, surface, 2.4 µg/L) but in the soft water sometimes exceeded an aquatic life criterion of 3 µg/L. After HOS, the long-term mean ΣCu dropped 12% to 2.9 µg/L (deep); surface concentrations were unchanged. Before HOS, bottom water ΣZn (mean = 17.7 µg/L) occasionally exceeded the criterion of 27 µg/L, but after HOS the long-term mean fell 36% to 11.3 µg/L. In contrast, ΣFe dropped 40-fold, dissolved Fe dropped 150-fold, ΣMn dropped 30-fold, and dissolved Mn dropped 400-fold. Fe and Mn declines were consistent with oxide precipitation. However, declines in Cu and Zn were due to homogenization of the deeper hypolimnion by mixing in the oxygenated HOS plume and not due to oxidation itself or the HOS-induced 79% reduction in algae. Important for reservoir management, HOS slightly reduced heavy metals in the reservoir outflows, benefiting the downstream river and fish hatchery. Similar results are predicted for mixing by aeration or propellers.